ADVERTISING MESSAGES FOR A FINANCIAL SERVICE PROVIDER: CREATION AND ANALYSIS OF THE EFFECTIVENESS - Grigore FUSU (Oradea Journal of Business and Economics, 2024)
The paper presents the process of creating and testing three advertising messages in order to select the most effective way to promote a non-banking financial company on a new targeted market represented by online retailers. As a result of a brainstorming session, three concepts were identified for the advertising message: satisfied entrepreneur, future concept, and the playful entrepreneur. Using each concept, three printed advertising messages were created. To test the advertising messages, research was conducted in two steps. The first step involved testing the messages through a quantitative survey based on a questionnaire administered to a sample of 28 employees of the company. This survey evaluated five dimensions of the prints: identification, relevance, capturing attention, intelligibility, and creativity. The second step aimed to test the efficiency of the prints using the Facebook Ads platform, measuring two metrics: CPM (cost per 1,000 impressions) and CTR (link click-through rate). The results of this research indicate that the advertising message based on the concept of the satisfied entrepreneur registered the best response in both testing methods.